REALIZING QUALITY EDUCATION AS A GOAL OF THE SUSTAINABLE DEVELOPMENT GOALS (SDGs) IN INDONESIA - Hasibuan, Muhammad Ilham (Universitas Airlangga, 2025)
Quality education is an important foundation in the development of a country. Quality education is a national goal stated in the preamble of the 1945 Constitution, which is to educate the nation's life. In addition to being a national goal, quality education is also a goal that must be achieved in accordance with the Sustainable Development Goals (SDGs) set by the United Nations (UN), which is the fourth goal. Indonesia has shown strong commitment to achieving these SDGs through various policies and programs. However, there are still many challenges to be faced, such as educational disparities between regions and among social groups, as well as the need for sustainable improvement in education quality. According to various reports, such as the Sustainable Development Report 2023, Indonesia's ranking is still relatively low. Similarly, the results of the Programme for International Student Assessment (PISA) 2022 released by the Organisation for Economic Co-operation and Development (OECD) show that Indonesia's scores are still declining and far from the global average score. Considering this situation, Indonesia needs strategies to achieve higher quality education.